O bibliotecário gestor: princípios da administração aplicados a unidade de informação - SANTANA, Escarlat dos Santos (2017)
This study approaches the thematic of the manager librarian, who, since their academic education, receive influences from and learn the management methods, showing it is of the utmost importance that the librarian knows and improves the principles and techniques of the administration, in order to base the management processes. Through a bibliographical research of qualitative character, this work discusses the relevance of the disciplines from the Administration area in the formation of librarians, so that they can apply this knowledge in the management of information centers. It concludes that the success of the manager librarian is directly related to how the administrator of an information center applies their knowledge on the development of their tasks, problem solving and conflict management in their work environment.